A new flexible lifetime model with log-location regression modeling, properties and applications. Issue 5 (4th July 2019) - Korkmaz, Mustafa C.; Altun, Emrah; Alizadeh, Morad; Yousof, Haitham M.
Abstract: In this paper, we propose a new lifetime model for modeling fatigue lifetime data. Some of its statistical properties are obtained. The method of maximum likelihood is used to estimate the model parameters. Simulation study is given to demonstrate the maximum likelihood estimators of the parameters of proposed model. Moreover, a new log-location-scale regression model is introduced with its residuals analysis. Three applications to real data sets are given to prove the usefulness of proposed model in real data modeling.